PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN SUSU SEGAR MOO DI KOTA BANDAR LAMPUNG - Ningrum, Intan Paramiarta; Sayekti, Wuryaningsih Dwi; Adawiyah, Rabiatul (Jurnal Ilmu-Ilmu Agribisnis, 2020)
This study aims to determine purchasing patterns, satisfaction levels, influence of service quality, product quality, and price perceptions of the satisfaction of Moo fresh milk consumers. The research was conducted by survey method at Chandra Department Store, Tanjung Karang. The research samples were recruited by accidental sampling. There were 50 households of Moo fresh milk consumers, in which respondents of this study were housewives. Data collecting was conducted in May-June 2018 and was analyzed by descriptive analysis, Customer Satisfaction Index Analysis (CSI), and verification analysis. The results of this study indicated that the type of purchase of Moo fresh milk was the most 1 liter. The volume of purchases of Moo fresh milk was mostly 1-3 litters per month with a frequency of purchases was 1-2 times per month. The score of Moo fresh milk consumer satisfaction was 80.43 percent, it meant that consumers were satisfied. Service quality and product quality had significant effects; unlike price perception had no significant effect on consumer?s satisfaction of fresh milk Moo.Key words: fresh milk, satisfaction, service quality